On the edge effect of composite materials - Soyuçok, A; Soyuçok, Z (WIT PRESS, 2000)
A half plane reinforced with a single semi-infinite layer is considered and it is supposed that at the edge of the reinforcing layer, continuously distributed normal forces -in self equilibrium- act. Using the exact equations of the linear theory of elasticity in the framework of the piecewise-homogeneous body model, the plane strain state is studied. The boundary conditions are satisfied exactly and the problem is reduced to the problem of a system of two singular integral equations.
Keywords: Materials Science